Effect of supplemented sugar in lysogeny broth medium on growth of Escherichia coli BL21(DE3) and recombinant protein production - Muenwongtham, Subongkod; Jaturapiree, Phimchanok; Pimviriyakul, Panu (Agriculture and Natural Resources, 2022)
Importance of the work: Escherichia coli BL21(DE3) is among the powerful hosts for recombinant protein expression. Varying approaches have been explored to improve the production of large amounts of recombinant protein. Objectives: To examine the effect of single sugar addition on the growth of E. coli BL21(DE3) and the production ability of recombinant green fluorescence protein (GFP) as a model for this study. Materials & Methods: Bacteria were cultured in Luria-Bertani broth (LB) media with supplemental sugars as additional carbon sources (2–10 g/L). Cell growth was monitored by measuring the optical density at 600 nm. Following the inducement of recombinant GFP expression by adding isopropyl β-d-1-thiogalactopyranoside, the content of soluble GFP was quantitated using two distinct methods: fluorescence detection and sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis. Results: The effect of sugar on the growth of E. coli BL21(DE3) could be classified into four groups of positive, negative, positive/negative and neutral effects, with a similar trend when pET-11a was included in the bacterial cells. Then, the expression of GFP under the optimum condition was determined in LB with the addition of the positive effect sugars (xylose or maltose). The addition of xylose or maltose in LB media significantly (p < 0.05) increased both cell growth by 2.0–2.5 fold and the production of recombinant GFP by 1.5–2.0 fold than those of the control and other sugars. Main finding: This study presented a proof of concept to improve the recombinant protein production in E. coli BL21(DE3) by adding a carbon source into traditional culture media without using engineered cells.